Hieronymain I, a New Cysteine Peptidase Isolated from Unripe Fruits of Bromelia hieronymi Mez (Bromeliaceae) - Bruno, Mariela Anahí (2003)
A new peptidase, named hieronymain I, was purified to homogeneity from unripe fruits of Bromelia hieronymi Mez (Bromeliaceae) by acetone fractionation followed by cation exchange chromatography (FPLC) on CM-Sepharose FF. Homogeneity of the enzyme was confirmed by mass spectroscopy (MALDI-TOF), isoelectric focusing, and SDS-PAGE. Hieronymain is a basic peptidase (pI > 9.3) and its molecular mass was 24,066 Da. Maximum proteolytic activity on casein (>90% of maximum activity) was achieved at pH 8.5-9.5. The enzyme was completely inhibited by E-64 and iodoacetic acid and activated by the addition of cysteine; these results strongly suggest that the isolated protease should be included within the cysteine group. The N-terminal sequence of hieronymain (ALPESIDWRAKGAVTEVKRQDG) was compared with 25 plant cysteine proteases that showed more than 50% of identity.